“LA ACCIÓN LÚDICA PARA DESARROLLAR LA COORDINACIÓN MOTRIZ GRUESA EN EL TERCER AÑO DE EDUCACIÓN GENERAL BÁSICA DE LA UNIDAD EDUCATIVA “ISABEL DE GODIN”. PERIODO 2018-2019”. - Pilco Martínez, Yadira Anabel (2019)
In the present investigative work it was possible to establish as a general objective: Determine the domain of the playful action in the development of gross motor coordination and as specific objectives: Identify how the Playful Action intervenes in the Development of gross motor coordination, Investigate the rationale Methodological theory on playful action and gross motor skills for the development of coordination in the children of the third year of Basic Education of the Educational Unit "Isabel de Godin". Propose recreational activities that promote the development of gross motor coordination. In the period of time in which the research project was developed, different topics were asked to address the problem in order to obtain more information. As a result, the results were obtained through the observation sheet, which determined by means of percentages the extent to which favored proposing different play strategies to improve the development of gross motor coordination. In order to detail the research, tables and graphs were elaborated with their respective analyzes and interpretations of the results. At the conclusion of the process of inquiry, conclusions were drawn up in which the remarkable improvement of the majority of children was evidenced by employing playful action in the development of gross motor coordination, therefore, it is recommended that teachers implement strategies on a daily basis. recreational and a semester analysis with the aim of obtaining an improvement in the learning process of the children of the Third Year of Basic Education of the Educational Unit "Isabel de Godin".